Granulosa Cell Tumor of Ovary with Anterior Abdominal Wall and Colonic Metastasis– A Case Report - Bista, Kumar Bahadur; Shrestha, Eliza; Ghimire, Sharmila; Gyawali, Pratik; Bhusal, Tapasya (Nepalese Journal of Cancer, 2026)
Among the various sex cord-stromal tumors, granulosa cell malignancy is the most common, representing approximately 2-5% of primary ovarian tumors. There are adult-type and juvenile-type histological variants of granulosa cell tumor. These lesions are mostly asymptomatic, and inhibin is an important tumor marker. A 29-year-old female with irregular bleeding for 3 months. She had a right salpingo-oophorectomy for an adnexal cyst, and histology had revealed an adult granulosa cell tumor. Abdominal wall and pelvic metastasis occurred at the time of the first visit to our hospital. She presented late and underwent chemotherapy and then debulking surgery. Regular follow-up is required to monitor recurrence.